Resveratrol Relieves Hyperoxia-Induced Brain Injury in Neonatal Rats by Activating Sirt1 - Kang, Lan; Dong, Wenbin; Li, Xiaobin; Ruan, Ying; Zhang, Rong (American Journal of Perinatology, 2020)
Objective Neonatal rats with hyperoxia-induced brain injury were treated with resveratrol to investigate its protective effects through analyzing changes in reactive oxygen species (ROS), Sirt1, p53, and acetylated p53 levels.Study Design Neonatal rats were randomly divided into hyperoxia and resveratrol intervened groups. Rats in both groups were placed in a hyperoxia chamber for 7 days to induce hyperoxia-induced brain injury. The rats in the resveratrol intervened group were administered resveratrol 60 μg/g body weight daily, whereas those in the hyperoxia group were administered a dimethyl sulfoxide-based solvent. Brain tissues were collected, and hematoxylin and eosin (H&E) and TUNEL staining, ROS measurements, real time-polymerase chain reaction, and western blotting were performed.Results H&E and TUNEL staining revealed increased cell damage and apoptosis in brain tissue from hyperoxia-exposed animals compared with the findings in animals in the resveratrol intervened group. Real time-polymerase chain reaction and western blotting identified increases in Sirt1 expression and decreases in p53 expression in the resveratrol intervened group. In addition, acetylated p53 protein expression was lower in the intervened group than in the hyperoxia group.Conclusion Resveratrol alleviated brain apoptosis induced by hyperoxia in neonatal rats by upregulating Sirt1-mediated pathways, suggesting its potentially beneficial role in the treatment of brain injury induced by hyperoxia.
Keywords: Sirt1; hyperoxia; brain injury; resveratrol